POTENCY OF RAMIN (Gonystylus bancanus Kurtz.) AND OTHER COMMERCIAL SPECIES IN PEAT SWAMP FOREST MANAGED WITH TPTI SILVICULTURAL SYSTEM IN BAGAN, RIAU - Hendromono, Hendromono (Indonesian Journal of Forestry Research, 2005)
Ramin  (Gonystylus bancanus Kurtz.)  is one  of  the  tree  species in  peat-swamp  forest  that  is endangered due to excessive exploitation. The objective of this research was to assess the potency of rarnin and other commercial tree species in primary and logged over peat-swamp forests at Bagan, Riau. The tree stands were inventoried in primary forest of the 2004 and 2006 Annual Work Plan (RKTs) and in  the  1997  and  2001  RKTs  managed  with  Indonesian  Selective Cutting  and  Planting  (TPTI) silvicultural system.  The  result  showed  that  rarnin in  Bagan peat-swamp  forest  was not  evenly distributed. The total number of ramin  in tree stage in primary forests was fewer than that in  logged over forests.  The total number of ramin species at tree stage in primary forest was between 4.5  and 5 trees ha· with the important value index (IVI) of 10.3  to 12.0%,  whereas the one at logged over forest were between 2.5 and 15  trees ha· with theM    indices of 7.9 to 20.4%.  Commercial species of swamp meranti (Shorea uliginosaand S. teysmaniana) and balam/ suntai or (Palaqqiumspp.) were dominant at tree stage both in the primary and the logged over forests. Enrichment in logged over forests is not needed since the total number of seedlings and saplings  is enough. The total number of potential core trees in logged over forests was enough for the next cutting cycle. The effort that must be done in logged over forests is to protect them from illegal logging.